Is there an important effect of the type of polyneuropathy on results of electromyography and pain - Korkmaz, Nilufer Cetisli; Akman, Tuba Can; Duray, Mehmet; Bilek, Furkan; Erdogan, Cagdas (Elsevier, 2021)
[Abstract Not Available]
25th World Congress of Neurology (WCN) -- OCT 03-07, 2021 -- Rome, ITALY